Halide Perovskite Heterostructures for High-Performance Light-Emitting Diodes - Huo, Yiming; He, Tingwei; Yang, Shaopeng; Jiang, Yuanzhi; Sun, Changjiu (Nano-Micro Letters, 2026)
Metal halide perovskites have emerged as highly promising candidates for the emissive layer in next-generation light-emitting diodes (LEDs) due to their narrow emission linewidths, high photoluminescence quantum yields, and tunable emission wavelengths. Achieving high-performance perovskite LEDs (PeLEDs) requires the emissive layer to possess efficient radiative recombination, low defect density, minimal ion mobility, and effective carrier confinement. Perovskite/perovskite heterostructure (PPHS) offers a compelling approach for engineering emissive layers with these desired attributes, owing to their ability to passivate surface defects, tailor bandgaps, and suppress ion migration. PeLEDs based on PPHS have demonstrated superior performance compared to single-phase devices, particularly in terms of external quantum efficiency and operational stability. This review provides a comprehensive overview of the typical PPHS architectures applied in PeLEDs, including vertical, lateral, and bulk configurations. We discuss representative fabrication strategies and the associated optoelectronic properties of these heterostructures, highlighting the mechanisms by which they enhance device efficiency and stability. Finally, we explore the remaining challenges and prospects for the application of PPHS in PeLEDs and other luminescent technologies. Highlights: 1 This review systematically summarizes the application of perovskite/perovskite heterostructures (PPHSs) in light-emitting diodes (LEDs), highlighting their critical roles in defect passivation, carrier confinement, lattice stabilization, and light management. 2 This review categorized PPHSs by dimensional combinations (e.g., 3D/3D, 2D/3D, 0D/3D) and spatial architectures—vertical, lateral, and bulk heterostructures—elucidating the structure-property relationships for efficient LEDs. 3 Key challenges and future directions are outlined, including advances in high-resolution characterization, carrier dynamics analysis, and controlled synthesis of PPHSs for next-generation optoelectronic applications.